GAMBARAN AKTIVITAS ENZYME ALANINE TRANSAMINASE (ALT) PADA PENGKONSUMSI MINUMAN BERALKOHOL - Ainun Qolbi Wasdili, Fini; Aslamiyah, Suaibatul; Romlah, Sitti (JURNAL KESEHATAN KARTIKA, 2023)
Alcohol consumption is the third largest risk factor in the world as a cause of disease and disability. There are various types of diseases caused by alcohol consumption, one of which is impaired liver function. Liver function disorders can be indicated by an increase in enzyme activity, one of which is the ALT enzyme. The purpose of this study was to describe the activity of the ALT enzyme in alcoholic beverage consumers. Examination of blood samples has been carried out on alcoholic drink consumers in the "X" community. The type of research conducted is a descriptive study and the method used in the ALT examination is enzimatyc kinetics IFCC. Process of written questionnaire, Informed Consent, as well as examination in the Laboratory. Examination of ALT enzyme activity was carried out at the FITKES UNJANI Laboratory using the Mindray BA-88A tool. This study used 30 samples from alcoholic drink consumers in the "X" community, the results obtained from the examination of ALT enzyme activity in alcoholic beverage consumers were then carried out data management. The results of the examination of 30 samples of alcoholic drinkers whose blood samples were taken 1 day after consuming alcoholic beverages showed abnormal ALT activity examination results in 2 people (7%) and normal results in 28 people (93%)